Comorbidities with non-small cell lung cancer: Is there an interdisciplinary consensus needed to qualify patients for surgical treatment? - Lembicz, Marta (Ann Thorac Med, 2018)
INTRODUCTION: Radical surgical treatment is the preferred action for patients with early-stage non-small cell lung cancer (NSCLC). Qualification for surgical treatment should consider a risk associated with the effect of comorbidities on the general condition of the patient. The aim of this article was an attempt to identify the risk factors for postoperative complications in patients treated for NSCLC, with a special focus on the coexisting diseases. METHODS: A total of 400 patients with NSCLC were included in this retrospective study. The incidence of postoperative complications (including major complications according to the European Society of Thoracic Surgeons [ESTS]) was analyzed. Factors associated with high risk of postoperative complications were identified. RESULTS: Postoperative complications occurred in 151 patients (39% operated patients), including severe complications according to ESTS in 75 patients (19%). From univariate analysis, risk factors for postoperative complications were arrhythmias, pneumonectomy, and open thoracotomy. According to ESTS, for major complications, the risk factors included age ≥65 years, the presence of comorbidities, hypertension, and arrhythmias. From multivariate analysis, the risk of complications was higher in patients undergoing pneumonectomy and with cardiac arrhythmias, whereas the risk of serious complications according to ESTS was found in people ≥65 years of age and suffering from comorbidities. CONCLUSIONS: The risk of postoperative complications is affected by both surgical factors and the general health of the patient. Elderly patients with chronic disease history, hypertension, and arrhythmias have an increased risk of postoperative complications. Knowledge of these factors will identify a group of patients requiring internal consultation and optimization of preoperative treatment and postoperative follow-up.